Internal quality assurance in universities: does NPM matter?. Issue 6 (3rd June 2019) - Agasisti, T.; Barbato, G.; Dal Molin, M.; Turri, M.
ABSTRACT: Following the ideas of New Public Management, Quality Assurance (QA) practices have become a relevant concern for public organizations. In the Higher Education sector, QA policies have inspired different reforms, becoming a debated issue for universities' leaders and policy-makers. This article analyzes the implementation of a newly defined committee for quality assurance (QAC) within Italian universities in order to identify if, as happened in other NPM reforms, it represents a further example of 'implementation gap'; and to detect the key variables that promote a satisfactory QAC functioning. Based on both the analysis of the composition and the role of QAC in all the Italian public universities and significant case studies, we have identified some core variables that promote the implementation of an effective QAC and ultimately supports the overall QA policy.